MOTHER’S KNOWLEDGE AND PARTICIPATION IN MEASLES RUBELLA (MR) IMMUNIZATION FOR TODDLERS - Haspita Rizki Syurya Handini; Yussie Ater Merry; Dhina Khairina (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2020)
Measles rubella (MR) immunization is to provide immunity against measles and rubella. To reduce measles and rubella, the government carried out the MR immunization campaign. The target of MR immunization achievement is at 95%; however, in West Sumatra Province it is still at 38,98% and Padang City is at 47%. The purpose of this study was to determine the determinant factor as participation in MR immunization for toddlers. This analytic survey used a cross sectional study design. The population was mothers who had toddlers with a sample of 86 respondents taken by proportional random sampling technique. The instrument used was a questionnaire. Data processing was analyzed by bivariate and multivariate using chi square test and logistic regression. The results of the bivariate analysis showed factors related to MR immunization, namely knowledge (p = 0.003), level of education (p = 0.006), and attitude (p = 0.006), while employment (p = 0,222) and number of children (p = 0,160) were not related to MR immunization and the most influential variable was the level of knowledge with p value 0.009 and OR 0.28. It can be concluded that knowledge, education and attitude are related to maternal participation in MR immunization with the most influential variable being knowledge. Therefore, there needs to be innovation in providing counseling to mothers and families about the importance of MR immunization.